A Computationally Inexpensive Battery Model for the Microscopic Simulation of Electric Vehicles - Schellenberg, Sebastian; Berndt, Rüdiger; Eckhoff, David; German, Reinhard (80th IEEE Vehicular Technology Conference Fall (VTC 2014-Fall), 2014)
The transition from classic combustion engine vehicles to electric vehicles is a major step to reduce worldwide CO2 emissions. In order to correctly and efficiently investigate impacts on the electric grid and the dimensioning of charging infrastructure, or to explore new technologies for a further increase of the driving range, realistic simulation models are required. In this paper, we present an accurate yet computationally inexpensive battery and kinematic model to be used in microscopic traffic simulation to help study the performance of thousands of electric vehicles. Our model also supports recuperation and range extender modules while only relying on the vehicle's speed and a set of constant predefined parameters. It can therefore be easily coupled with current sophisticated traffic simulators. We show its applicability and correctness regarding the State of Charge and power flows using comprehensive real-life experiments.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.acompu
Keywords: Electromobility; IVC; lithium-ion battery model

A Lightweight Simulation Framework for the Analysis of Electrified Vehicle Fleets - Berndt, Rüdiger; Schellenberg, Sebastian; Eckhoff, David; German, Reinhard (81th IEEE Vehicular Technology Conference Spring (VTC 2015-Spring), 2015)
Replacing combustion vehicles with electric vehicles is a major step towards reducing CO 2 emissions. With regard to this shift, in particular commercial or governmental vehicle fleets are believed to be early adopters. However, the electrification of vehicle fleets is a complex task since it can have a huge impact on companies’ day-to-day-business. This article presents a lightweight simulation framework to support the planning process and to study important effects of vehicle fleet electrification. Our discrete event-based approach allows to investigate economical and environmental aspects, such as the impact on operating costs, the required electric energy, or the amount of CO 2 emissions. Based on a given trip schedule (consisting of start time, distance, and duration), the framework allows deriving all necessary information, among others to dimension both the vehicle fleet and the charging infrastructure. We show the usefulness and the capability of our model by presenting results for a mid-sized company’s vehicle fleet comprising 100 vehicles.
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD7.alight
Keywords: Electromobility; Discrete Event-based Simulation

An Energy Demand Model for the Microscopic Simulation of Plug-In-Hybrid Vehicles - Ammon, Lorenz; Huber, Bernd; Hübler, Florian; Berndt, Rüdiger; Schellenberg, Sebastian; Schneider, Vitali (Proceedings of the 2016 IEEE Transportation Electrification Conference and Expo (ITEC 2016), 2016)
More and more car manufactures are combining a normal combustion engine and an electric motor to satisfy the standards for CO2 emissions. In order to take advantage of this technology in the most efficient way, for example in companies car fleets, realistic simulation models are required. In this paper, we present an accurate yet computationally inexpensive energy demand model for the microscopic simulation of plug-in hybrid vehicles. Our model mostly consists of a combustion engine, an electric motor and, most importantly, a realistic engine management model. Furthermore, a pragmatic kinematic model as well as a model for recuperation of energy while breaking are provided. Modularly designed, our simulation model allows for simple replacement and adjustment of each module. As input values, our model only requires the vehicle's speed and a set of constant predefined parameters. Consequently, this also enables the model to be easily connected with current sophisticated traffic simulators. We show the correctness of our model regarding the consumption of fuel and electric energy using comprehensive real-world experiments.
Keywords: Mathematical model; Object oriented modeling; Electromobility; Plug-in Hybrid Electric Vehicle; Simulation

Comparison of Application and Network Layer Name Resolution in Mobile Ad hoc Networks - Schellenberg, Sebastian; Krug, Silvia; Eckert, Jürgen; Seitz, Jochen (12th ACM Symposium on Performance Evaluation of Wireless Ad Hoc, Sensor, and Ubiquitous Networks (PE-WASUN 2015), 2015)
In disaster scenarios, communication systems usually consist of heterogeneous nodes and partially damaged infrastructure. Communication is important for rescue teams and victims as well but a serious problem because normal network systems like wired or mobile radio Internet could be unreliable or simply not available. To deal with these problems, much effort has been spent on Mobile Ad hoc Networks ( MANET s) and their specialties. Those networks are usually unsteady and highly mobile. Therefore, classical network services like the resolution of names to their corresponding local IP addresses is a big challenge. In this paper, we will compare different MANET-adapted name resolution approaches located in the Application and Network Layer by simulations using the Network Simulator 3 ( ns-3 ) and discuss their performance and fields of application.
UnivIS-Import:2015-10-26:Pub.2015.tech.IMMD.IMMD7.compar
Keywords: Mobile Ad hoc Networks; Name Resolution; Reactive Routing; Proactive Routing

Evaluating the Electrification of Vehicle Fleets Using the Veins Framework - Schellenberg, Sebastian; Berndt, Rüdiger; German, Reinhard; Eckhoff, David (Proceedings of the 1st OMNeT++ Community Summit 2014, 2014)
The simulative performance evaluation of future Intelligent Transport Systems (ITSs) is a challenging task. New mobility patterns, induced by car sharing or autonomous vehicles, the switch towards electric or hydrogen vehicles, and the communication between vehicles (and infrastructure) are believed to change road traffic as we know it. Investigating new applications and protocols, or finding answers to strategic questions—like the optimal placement of charging infrastructure—is often done by means of simulation. The biggest challenge is the development of realistic models that are required for these simulations in order to produce meaningful results. The case study discussed in this paper involves a company maintaining a vehicle fleet of one hundred vehicles. In this article we will discuss how we extend and deploy the Veins framework, which couples OMNeT++ and SUMO, to help in the process of electrifying this vehicle fleet, i.e., replacing combustion engine cars with electric vehicles to save money and lower CO 2 emissions.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.evalua_5
Keywords: E-Mobility; Simulation; IVC

How Electric Vehicles Can Benefit from Vehicular Networking - Schellenberg, Sebastian; Berndt, Rüdiger; Eckhoff, David; German, Reinhard (3rd GI/ITG KuVS Fachgespräch Inter-Vehicle Communication (FG-IVC 2013), 2015)
Wireless exchange of information between vehicles or vehicles and infrastructure nodes is believed to both improve traffic safety and traffic efficiency. Another trend that can currently be observed is a growing market share of electric vehicles. Unfortunately, electric vehicles still suffer from limited driving ranges and long charging times. In this paper, we not only show possible applications to alleviate these problems by the help of wireless communication but also point to models and tools necessary for their evaluation. We especially discuss how – when a vehicle is aware of its surroundings and able to predict the behavior of other vehicles or traffic lights – it can potentially optimize the process of recuperation, that is, the charging of the battery when braking. Furthermore, we show that vehicular communication can be beneficial to optimize charging strategies or job dispatching in vehicle fleets.
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD7.howele
Keywords: Electromobility; Vehicular Communication; Discrete-Event Simulation